BUNA-CREDINȚĂ ÎN ACTIVITATEA JUDECĂTORULUI - Cozma, Daniela (SUPREMANCE OF LAW, 2016)
Good faith in the activity of the judge. The article includes an etymological, terminological and historical analysis of the concept of good faith in order to specify its peculiarities and role in the activity of the judge.
Keywords: good faith; Judge; principle; justice; diligence; loyalty